1977
DOI: 10.1002/ana.410020505
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors in children with serious motor and mental handicaps

Abstract: Fifty children with marked neurological abnormality manifested by moderate or severe motor disability and severe mental retardation were compared with a large control population with respect to prospectively ascertained perinatal characteristics. None of 60 prenatal factors distinguished the affected group from controls. In labor and delivery, lowest fetal heart rate in the second stage of labor, arrested progress of labor, and use of midforceps discriminated between the two groups. Neonatal characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
10

Year Published

1979
1979
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 8 publications
0
23
1
10
Order By: Relevance
“…The tonic phase was associated with apnea and urinary incontinence. The tonic posture and apneic episodes lasted for [3][4][5] min. Thereafter, tonic-clonic seizures commenced with associated swimming-like movements which continued until interrupted by another tonic or clonic fit.…”
Section: Institutional Approvalmentioning
confidence: 99%
See 1 more Smart Citation
“…The tonic phase was associated with apnea and urinary incontinence. The tonic posture and apneic episodes lasted for [3][4][5] min. Thereafter, tonic-clonic seizures commenced with associated swimming-like movements which continued until interrupted by another tonic or clonic fit.…”
Section: Institutional Approvalmentioning
confidence: 99%
“…On the othe~. hand, both published and unpublished experimental studies in immature animals of most, although not all, species have failed to demonstrate that even prolonged seizures (status epilepticus) lead to overt brain injury (1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14] (see "Discussion").…”
mentioning
confidence: 99%
“…The authors' previous study 59 of CBF following asphyxial insult of 15 minutes demonstrated profound decreases in flow to all cerebral regions examined. Based on the predictive value of a low 5-minute Apgar score 25 and the practical time of instituting life-saving support measures, 60 5 minutes of asphyxia followed by a 5-minute resuscitation phase were chosen for this experiment. Drug (i.e., nimodipine) was administered as soon as might be practically possible.…”
Section: A6a1mentioning
confidence: 99%
“…35 We investigated the influence of the thromboxane synthesis inhibitor CGS 13080 on CBF and metabolism in newborn beagle pups exposed to perinatal asphyxia. Based on the predictive value of a low 5-minute Apgar score 36 and the practical time of instituting life-saving support measures, 37 5 minutes of asphyxia was chosen for these experiments. For saline-treated pups, insult produced marked increases in CBF to the medulla, midbrain, and pons; CBF fell in cortical gray structures.…”
Section: Discussionmentioning
confidence: 99%